Evaluation of an optimized protocol using human peripheral blood monocyte derived dendritic cells for the in vitro detection of sensitizers: Results of a ring study in five laboratories. Issue 5 (August 2015) - Reuter, Hendrik; Gerlach, Silke; Spieker, Jochem; Ryan, Cindy; Bauch, Caroline; Mangez, Claire; Winkler, Petra; Landsiedel, Robert; Templier, Marie; Mignot, Aurelien; Gerberick, Frank; Wenck, Horst; et al.
Highlights Ring study in five laboratories evaluating the performance of an optimized in vitro test system. In vitro test system based on peripheral blood monocyte derived dendritic cells. Successful transfer of the test protocol to all participating laboratories. Correct assessment of the sensitization potential of the tested set of chemicals.